Trajetórias estaduais da educaç\~ao pública no Brasil sob a lente do Índice de Desenvolvimento da Educaç\~ao Básica - Herton Ellery Araújo; Ana Luiza Machado de Codes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– The covid-19 pandemic disrupted the way of delivering education in many countries around the world. Currently, we are experiencing several consequences of that period. The most notable and widespread problem concerns school performance. Even when there is progress in student learning in the post-pandemic phase, the pace is slow and quite variable within a country. In this context, to monitor the progress of student performance in state-public education systems in Brazil, this paper uses information from the Basic Education Development Index (Índice de Desenvolvimento da Educaç\~ao Básica - Ideb) from the last ten years, distinguishing two distinct phases: from 2013 to 2019, when public policy was the main factor in the general organization of education; and from 2020 to 2023, when the pandemic greatly affected teaching and learning methods. Based on the trajectories of the states outlined by the data, it is possible to discern some points, which are presented and commented on throughout the text, that deserve greater attention. It is recommended that each Federative Unit (Unidade da Federaç\~ao - UF) reflects on its past and present educational decisions and policies, to direct them appropriately and, thus, offer quality education to the citizens.
Keywords: I28; 330; education; student performance; states